EVALUATING CHILD WELFARE ASSISTANCE IN JAKARTA: A CASE STUDY OF THE KARTU ANAK JAKARTA PROGRAM - Suhailla Sekar Ayu; Susilawati Susilawati; Dwi Yuliani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2026)
Child poverty in urban areas is a multidimensional crisis demanding high-precision policy interventions to break the chain of deprivation. This study aims to evaluate and optimize the Kartu Anak Jakarta (KAJ) policy in fulfilling the basic rights of underprivileged children in East Jakarta. Using a convergent parallel approach, the study involved 141 beneficiaries drawn through proportional stratified random sampling and 12 purposive informants. Data collection utilized scaled questionnaires, in-depth interviews, and observation. Performance measurement referred to William N. Dunn's six criteria, validated through Pearson statistics, Cronbach's Alpha reliability, and source triangulation. The findings reveal that KAJ operates effectively as a biological shield for subsistence nutrition. However, the program experiences structural failure in the educational dimension and triggers economic deficits due to the nominal assistance being eroded by urban inflation. Furthermore, weak supervision triggers high practices of fund diversion (fungibility) for non-child needs. Therefore, optimizing this policy urgently requires amending institutional governance regulations to transform transactional monitoring into functional supervision (case management), and mandating the formation of cross-sectoral working groups to ensure the integrative fulfillment of children's rights.